PENGARUH PENGANGGURAN, PENDIDIKAN, JUMLAH PENDUDUK TERHADAP TINGKAT KEMISKINAN PROVINSI JAWA TIMUR TAHUN 2002-2021 - Khurrotun Ayunin; Mega Tunjung Hapsari (Lafadz Jaya Publisher, 2023)
This study determines the effect of unemployment, education, total population on poverty levels in East Java province. Using this type of associative research using a quantitative approach, the data used is secondary data using time series data over a period of 20 years (2002-2021). This study uses a multiple linear regression analysis model. The results of this study are that the unemployment variable has a positive effect on poverty, while the education and population variables have a negative effect on poverty. The results of the simultaneous test (F Test), namely the variables unemployment, education, and population simultaneously or jointly affect poverty in East Java Province.